NGOs as Social Movements: Policy Narratives, Networks and the Performance of Dalit Rights in South India. Issue 1 (7th September 2020) - Mosse, David; Nagappan, Sundara Babu
ABSTRACT: Donor‐funded development NGOs are sometimes portrayed as co‐opting, privatizing or depoliticizing citizen action or social movements. This much is implied by the term 'NGOization'. Alternatively, NGOs can be seen as bearers of rights‐based work increasingly threatened by tighter regulation or substitution by corporate social responsibility models of development. This article engages critically with both perspectives. It traces the role of NGOs and their funders in agenda setting, specifically in bringing the previously excluded issue of caste discrimination into development policy discourse in the form of a Dalit‐rights approach in Tamil Nadu, south India. The authors explore the institutional processes of policy making and NGO networking involved, the alliances, entanglements of NGOs and social movements, and the performativity of NGO Dalit rights. But at the same time, the article illustrates how NGO institutional systems have constrained or failed to sustain such identity‐based claims to entitlement. In Nancy Fraser's terms, the article explores success and failure in addressing 'first‐order' issues of justice, that is rights to resources (in this case, land), and in tackling 'second‐order' injustices concerning the framing of who counts (who can make a claim as a rights holder) and how (by what procedures are claims and contests staged and resolved). This draws attention to the important but fragile achievements of NGOs' discursive framings that give Dalits the 'right to have rights'.